EFFECT OF BODY MASS INDEX, WAIST HIP RATIO AND WAIST CIRCUMFERENCE ON COGNITIVE FUNCTIONS IN PERIMENOPAUSAL WOMEN - NAYANATARA AK; SHAMEEMA S M; SHAILA MD; BHAGYALAKSHMI K; ANUPAMA N; REKHA D KINI; SNEHA B SHETTY; SHEILA R PAI (International Journal of Pharma and Bio Sciences, 2013)
Cognitive performance is predictive of subsequent dementia; the assessment of risk factors might have a protective or detrimental effect on cognitive performance in perimenopausal women.The objective of the present study was to elucidate the effect of BMI, waist circumference and waist hip ratio on various cognitive function parameters such as Mini Mental Scale examination (MMS-E), Orientation, Attention, Memory, Visuo Spatial ability, Verbal Fluency and Language in perimenopausal age women.The present study included a total of 60 healthy women (40-60 years). Participants were categorized into control group and overweight/obese groups based on the body mass index . The results of the present study showed a significant decrease (P<0.05) in all the cognitive parameters in the overweight/obese group when compared to the control group. In conclusion the present study suggest that increased waist circumference, waist hip ratio and BMI are the risk factor for cognitive impairment in perimenopausal women.